2007
DOI: 10.1080/00016340701415509
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two techniques for the evaluation of fetomaternal hemorrhage in RhD‐negative women: gel agglutination and haemoglobin F determination by flow cytometry

Abstract: The gel agglutination technique, as used in the range of 0.1-10 ml, is not sensitive enough to detect FMH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…FMH was greater than 10 mL in 3 cases by KB, whereas by the microcolumn gel method FMH was at least 7.2 mL. This was in accordance with a study conducted by Ben-Haroush et al, 8 who found four episodes of FMH greater than 10 mL detected by flow cytometry and only one episode that was detected by gel agglutination method. Hence, for large-volume FMH, KB is required for FMH estimation, and the microcolumn gel method is not the test of choice.…”
Section: Discussionsupporting
confidence: 90%
“…FMH was greater than 10 mL in 3 cases by KB, whereas by the microcolumn gel method FMH was at least 7.2 mL. This was in accordance with a study conducted by Ben-Haroush et al, 8 who found four episodes of FMH greater than 10 mL detected by flow cytometry and only one episode that was detected by gel agglutination method. Hence, for large-volume FMH, KB is required for FMH estimation, and the microcolumn gel method is not the test of choice.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the use of monoclonal antibodies (e.g., anti-HbF) that we used in our study ensures high specificity and repeatability of the reaction with the antigen, making cytometric tests specific and sensitive. Due to their high specificity, immunoglobulins may be used at very low concentrations, eliminating the tendency to cross-react with other proteins and non-specific binding [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that their gel agglutination card assay had comparable sensitivity with the acid-elution staining assay and detected all admixtures of D+ RBCs that were greater than 0.2 percent. 28,29 Ben-Haroush and colleagues 30 analyzed blood samples from 118 D-postpartum women for fetal RBCs by both gel agglutination and flow cytometry (anti-HbF), and reported that the gel agglutination test failed to detect FMHs reliably in the range of 0.1 to 10.0 mL. Subsequently, Agaylan and colleagues 31 described a particle gel immunoassay using superparamagnetic particles coated with monoclonal anti-D.…”
Section: Gel Agglutination Cardsmentioning
confidence: 99%